The Alternative Media Supporting the Protocorm and Plantlet Growth of the Indonesian Black Orchid (Coelogyne pandurata Lindl.) Grown In Vitro - Rindang Dwiyani; Yuyun Fitriani; Ixora Sartika Mercuriani (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Due to the high cost of the most often used basic media in tissue culture, it is vital to identify more affordable alternatives. This research aimed to determine the best alternative culture media for the protocorm and plantlet growth of Coelogyne pandurata Lindl. It employed a completely randomized design, eight treatments and four replications. The treatments referred to the different types media and consisted of M1 = New Phalaenopsis (NP) medium, M2 = a medium made from foliar fertilizer (FFM), M3 = NP + 2 cc L-1 AB mix solution (a media for hydroponics), M4 = FFM + 2 cc L-1 AB mix solution, M5 = NP + 50 cc L-1 of tomato extract, M6 = NP + 50 cc L-1 of bean sprout extract, M7 = FFM + 50 cc L-1 of tomato extract and M8 = FFM + 50 cc L-1 of bean sprout extract. The M4 medium exhibited the best results in terms of average leaves count (4.80), average shoot length (2.68 cm), average root length (4.35 cm), the average fresh weight per plantlet (214.5 mg) and dry weight of plantlets (73.1 mg). The average number of roots per plantlet was 4.25, acquired using the less expensive M8 treatment, which also produces a negligible number of leaves (4.50). In conclusion, the M4 medium is the most appropriate medium for growing protocorm and plantlet of C. pandurata. The experiment also found that the FFM basic medium combined with 50 cc L-1 of bean sprout extract can be used as another cheaper alternative for growing protocorms of C. pandurata.